Release of nickel and chromium ions from stainless steel brackets as a result of long-term exposure to commonly used toothpaste - Kriswandini, Indah Listiana; Bagus, Agastya Perkasa Ida (Indonesian Journal of Dental Medicine, 2024)
Background: Brackets in fixed orthodontic appliances are mostly made from metal or stainless steel. Maintaining oral hygiene by brushing the teeth with toothpaste during orthodontic treatment is important. One of the ingredients in toothpaste, sodium fluoride, can cause degradation of the stainless-steel surface, which has the potential to corrode or release metal elements. Purpose: the purpose of this study is to describe the Nickel and chromium ion release of stainless-steel brackets against toothpaste use in orthodontic treatment by means of narrative review. Review: The main corrosion products of stainless-steel brackets are nickel and chromium. Toothpaste detergents contain sodium lauryl sulfate, which can cause the release of nickel ions due to the presence of sodium ions, which can trigger redox reactions. In addition, the fluoride content will combine with hydrogen to produce hydrofluoric acid, which can damage the oxide layer on orthodontic wires, resulting in the release of metal ions such as nickel and chromium. The effects of the release of these ions can be carcinogenic, cause hypersensitivity reactions, and cause cytotoxicity. Corrosion causes the dissolution of filler metal, resulting in weakened bracket material and increased friction, leading to delayed tooth movement. Conclusion: Toothpaste can affect the release of nickel and chromium ions in stainless steel brackets in the presence of sodium and fluoride.